(untitled) (Journal of Academic Research, 2025)
BACKGROUND It is rare for giant cell tumor to occur in the distal fibula and there is no consensus on the modality of management of such tumor CASE SUMMARY A 48 -old woman who had a long-standing history of pain and swelling of the right lateral malleolus presented to our hospital. imaging revealed a 7 cm x4 cm cystic expansile lytic lesion occupying the lateral malleolus. The biopsy obtained by excising the mass confirmed it was a giant cell tumor. The patient was a known case of End Stage Renal Disease, after consulting anesthesia regarding patient preparation for surgery and considering treatment options with the patient we proceeded to preform excision of the mass and tibiotalar fusion, which performed well in the 6-month period of follow up with the patient CONCLUSION Tumor resection of the distal fibula and tibiotalar fusion of the ankle is a successful option for the management of such case